2015
DOI: 10.1101/cshperspect.a021790
|View full text |Cite
|
Sign up to set email alerts
|

Memory Retrieval in Mice and Men

Abstract: Retrieval, the use of learned information, was until recently mostly terra incognita in the neurobiology of memory, owing to shortage of research methods with the spatiotemporal resolution required to identify and dissect fast reactivation or reconstruction of complex memories in the mammalian brain. The development of novel paradigms, model systems, and new tools in molecular genetics, electrophysiology, optogenetics, in situ microscopy, and functional imaging, have contributed markedly in recent years to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 321 publications
3
30
0
Order By: Relevance
“…Behavioural and neuroscientific studies primarily in adults identified a host of different factors why interindividual differences emerge. Such factors are, among others, working memory capacity (e.g., the function to maintain a limited amount of information in the presence of distraction; Unsworth & Engle, ), emotional arousal (McGaugh, ), memory strategies (Unsworth, ), knowledge (Ericsson & Kintsch, ), degree of learning (Loftus, ; Slamecka & McElree, ) (Unsworth, ; Unsworth, Spillers, & Brewer, ), and neurophysiological features like the amount of baseline dopamine release (Cools & D'Esposito, ), fibre density (Kanai & Rees, ), and associated differences in neural activity and communication between brain areas relevant for encoding and consolidation of the information (Ben‐Yakov, Dudai, & Mayford, ; Fell & Axmacher, ; Hermans et al ., ; Shrager, Kirwan, & Squire, ; Tambini et al ., ; Wislowska, Heib, Griessenberger, Hoedlmoser, & Schabus, ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural and neuroscientific studies primarily in adults identified a host of different factors why interindividual differences emerge. Such factors are, among others, working memory capacity (e.g., the function to maintain a limited amount of information in the presence of distraction; Unsworth & Engle, ), emotional arousal (McGaugh, ), memory strategies (Unsworth, ), knowledge (Ericsson & Kintsch, ), degree of learning (Loftus, ; Slamecka & McElree, ) (Unsworth, ; Unsworth, Spillers, & Brewer, ), and neurophysiological features like the amount of baseline dopamine release (Cools & D'Esposito, ), fibre density (Kanai & Rees, ), and associated differences in neural activity and communication between brain areas relevant for encoding and consolidation of the information (Ben‐Yakov, Dudai, & Mayford, ; Fell & Axmacher, ; Hermans et al ., ; Shrager, Kirwan, & Squire, ; Tambini et al ., ; Wislowska, Heib, Griessenberger, Hoedlmoser, & Schabus, ).…”
Section: Discussionmentioning
confidence: 99%
“…At its core, retrieval can be considered as the reinstatement or reconstruction of information that was encoded in memory (Dudai 2015). With the ability to measure large-scale neural networks involved in retrieval, researchers studying memory in humans are able to consider not only where features of encoded memories are "stored" in the brain, but which regions and processes contribute to what is successfully remembered (and in how much detail).…”
Section: Episodic Memory Retrievalmentioning
confidence: 99%
“…23,24 Consolidation is the process by which a memory becomes enduring over the long term. [24][25][26] To understand consolidation, it is critical to recognize that the processes of encoding, consolidating, and retrieving memories is not a static process of information storage but rather a constructive and reconstructive process in which memory is constantly changing. [24][25][26] Memory processing involves encoding as a representation of the stimulus is created in the brain.…”
Section: How Does Retrieval Practice Work?mentioning
confidence: 99%
“…24,25 The memory then undergoes consolidation over time as the representation becomes reorganized and distributed within the neocortex. [23][24][25][26] This process is thought to occur through ongoing interactions between the hippocampus and the neocortex resulting in a memory that is less dependent on the hippocampus. [23][24][25][26] Consolidation occurs as memories are reactivated in the cortex and integrated with preexisting circuits.…”
Section: How Does Retrieval Practice Work?mentioning
confidence: 99%